Penerapan Hukum Adat Terkait Sengketa Tanah Wida Antara Masyarakat Kampung Lawir Dan Masyarakat Kampung Kakor Kecamatan Langke Rembong Kabupaten Manggarai Nusa Tenggara Timur - Thoe, Maria Suryati Dorman; Mauritsius, Darius; Dju Bire, Chatryen M (Artemis Law Journal, 2025)
This empirical legal research investigates a land dispute in Indonesia between the Lawir village community (descendants of Rona) and the Kakor village community (descendants of Wina), originating from a land grant to Wina upon her marriage. The study identifies the factors causing this potential conflict and examines the provisions of customary law in its resolution. Data was collected through interviews and literature review, and analyzed descriptively-qualitatively. The findings reveal that the dispute is triggered by the Kakor community's desire to sell the land, the absence of formal ownership documents, and the Lawir community's intent to reclaim the land for public facilities. The customary law resolution involves the Traditional Elder mediating through a process called "Leko wase." This process includes an offering ("kapu manuk lele tuak") followed by a ritualistic invocation ("kepok") and culminates in both parties jointly demarcating the land boundaries with symbolic markers. This study highlights the role of customary law in resolving land disputes in the absence of formal legal frameworks.